Preferred methods of analysis for chemical tracers in moderate- and high-temperature geothermal environments - Kroneman, R.L.; Yorgason, K.R.; Moore, J.N. (Utah Univ. Research Inst., Salt Lake City (USA). Earth Sciences Lab., 1984)
This report describes the sampling and analytical techniques used for tracer analysis in the Raft River and East Mesa field tests. The collection procedures and sample preservation techniques, analytical methods and possible sources of contamination or error are discussed in detail. 6 refs.